A Fully-Integrated CMOS LDO Regulator for Battery-Operated On-Chip Measurement Systems. (2016) - Pérez-Bailón, J.; Márquez, A.; Calvo, B.; Medrano, N.; Martínez, P.A.; Sanz-Pascual, M.T.
Abstract: This paper presents a fully-integrated 0.18 μm CMOS low drop-out (LDO) regulator designed to drive on-chip low power front-end sensor nodes. The proposed LDO is based on a simple telescopic amplifier stage with internal cascode compensation driving a PMOS pass-device, providing a high precision 1.8 V output voltage for input voltages from 3.6 V to 1.92 V up to a 50 mA load current with only 22 μA quiescent current. Line and load regulation are respectively better than 0.017 mV/V and 0.003 mV/mA, while recovery times are below 4 μs over a (-40 °C, 120 °C) temperature span.